To hear One's breath: Unveiling the eponymous quartet - A historical exploration of the eustachian tube - Robert Hage; Kevlian Andrew (Elsevier, 2024)
Purpose: A real-life experience of the effects of a patulous Eustachian tube (ET) by one of the authors led to a search into this condition. This resulted in the 'discovery' of four eponymous anatomical structures related to the ET, the origins of which were not well known. The authors conducted a literature review to provide a historical account of this eponymous quartet as an homage to their contributions to the fields of anatomy and otology. Methods: Applying 'patulous Eustachian tube' as the search criterium yielded a total of 258 articles on PubMed search, and 1930 on Google Scholar on September 19th, 2023. During this process, the search criterium was subsequently narrowed to the names of four physicians who were found to have an eponymous relationship to structures of the Eustachian tube: Ostmann, Rüdinger, Von Tröltsch and Weber-Liel. These researchers were individually investigated with consideration given to different variations in spelling. The findings were tabulated and are narrated in the discussion. Results: Four eponymous anatomical structures closely related to the ET, being Ostmann fat pad, Rüdinger safety space/canal, Von Tröltsch fascia and Weber-Liel fascia were found. Ostmann fat pad was referenced most frequently. Although easily recognizable on histological slides, it is rarely mentioned in textbooks. Von Tröltsch, more popularly known for his various contributions to otolaryngology, lends his name to the salpingopharyngeal fascia. Weber-Liel is linked to the lateral fascia of the tensor veli palatini muscle. All four researchers were German physicians with a special interest in otology. The work of these individuals is presented as a snapshot of a remarkable time during the latter part of the nineteenth century. Conclusion: Though the Eustachian tube has been discussed for centuries, four remarkable researchers contributed to the general knowledge of this structure during the nineteenth century. Paul Ostmann's fat pad of the Eustachian tube is the most referenced of the four, with little mention of Nikolaus Rüdinger's safety canal in the literature. Anton Von Tröltsch's salpingopharyngeal fascia and Friedrich Eugen Weber-Liel's fascia found between the medial pterygoid and tensor veli palatini muscles are eponymously linked without clear indication of the origin of these connections being found in the literature. The contribution of these physicians, however, extends beyond their work on the Eustachian tube and includes the creation of tools and the establishment of journals specific to furthering the body of work on otolaryngology. Recognition should be given to the names Ostmann, Rüdinger, Von Tröltsch and Weber-Liel for their accomplishments in increasing the knowledge of structures related to the eustachian tube.